2004
DOI: 10.1002/ptr.1535
|View full text |Cite
|
Sign up to set email alerts
|

Plants used by a Quilombola group in Brazil with potential central nervous system effects

Abstract: This study focused on an ethnopharmacological survey among a group of Brazilian Quilombolas (descended from runaway slaves living in hideouts up-country) whose therapeutic practices involve a combination of healing ceremonies and prescription of medicinal plants consisting of the use of, at least, 48 plants with possible effect on the central nervous system (CNS), cited in 53 formulas prescribed for 17 therapeutic indications, the main ones being: to fortify the brain, for insomnia, as a sedative, for insanity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 23 publications
(19 reference statements)
1
18
1
3
Order By: Relevance
“…In a review focused on plants possibly acting/having effect on CSN indicated by 26 native Brazilian ethnicities , it was observed that families with the highest frequency of reporting were Fabaceae, Asteraceae, Rubiaceae and Solanaceae, among others. Two other ethnopharmacological studies with the same focus as this review verified that the Fabaceae, Sterculiaceae, Asteraceae and Rubiaceae families Giorgetti et al are also present among reports given by members of the Krahô tribe (Rodrigues & Carlini, 2005); while Asteraceae is dominant among the Sesmaria MataCavalos quilombola (Rodrigues & Carlini, 2004). In a review study on psychoactive plants used by Mexican indian tribes (Díaz, 1977), it was also observed that among the most frequently mentioned families, the Solanaceae, Asteraceae and Fabaceae families were to be found.…”
Section: Resultssupporting
confidence: 70%
“…In a review focused on plants possibly acting/having effect on CSN indicated by 26 native Brazilian ethnicities , it was observed that families with the highest frequency of reporting were Fabaceae, Asteraceae, Rubiaceae and Solanaceae, among others. Two other ethnopharmacological studies with the same focus as this review verified that the Fabaceae, Sterculiaceae, Asteraceae and Rubiaceae families Giorgetti et al are also present among reports given by members of the Krahô tribe (Rodrigues & Carlini, 2005); while Asteraceae is dominant among the Sesmaria MataCavalos quilombola (Rodrigues & Carlini, 2004). In a review study on psychoactive plants used by Mexican indian tribes (Díaz, 1977), it was also observed that among the most frequently mentioned families, the Solanaceae, Asteraceae and Fabaceae families were to be found.…”
Section: Resultssupporting
confidence: 70%
“…O conhecimento e o respeito às noções de saúde que cada comunidade possui são necessários, uma vez que muitas vezes estas não concordam com os paradigmas da medicina ocidental, mas regem a vida das comunidades e possuem sua própria eficácia. Ao agir com esta consciência, a nação verá de fato o controle social do SUS e, conseqüen-temente, um melhor resultado em suas abordagens do aspecto inclusivo 9,30,[34][35][36] . A Fonoaudiologia vem buscando sua inserção definitiva e plena junto às várias diretrizes estabelecidas pós SUS, onde intenciona participar dos processos preventivos e curativos desde sua origem.…”
Section: Saúde E Quilombolasunclassified
“…In two studies conducted in the state of Rio de Janeiro, one in Rio city (Azevedo & Silva) and one in the reservation of Mangaratiba (Medeiros et al, 2005), the Asteraceae and Lamiaceae family of plants were the most frequently cited, the same happening in Conceição Açú-MT (Pasa et al, 2005). Species from the Asteraceae family were also the most frequently noted for medicinal use in a survey done in Ingaí-MG (Botrel et al, 2006) and by a "quilombola"(community of people descended from former Brazilian slaves), among the plants with possible action in the central nervous system (Rodrigues & Carlini, 2004). These data suggest that the Asteraceae and Lamiaceae family have excellent pharmacological potential on different kinds of diseases and they are currently being investigate in many clinical studies.…”
Section: Ethnobotanical Search For Tr Plant Ligandsmentioning
confidence: 86%